The Effect of Dried Noodle with Patin Fish and Pumpkin Flour on Body Weight of Children - Fitriani Fitriani; Yuniarti Yuniarti; Dyah Subandriani (International Journal of Nutrition Sciences)
Background: Programs targeting malnutrition in toddlers are critical for preventing undernutrition and mitigating more severe health complications. The substitution with high-protein local-ingredients into noodle products can offer a promising strategy. Dried noodles enriched with Patin fish and pumpkin flour present a viable alternative for supplementary feeding programs. Assessing their effectiveness is essential to optimize supplementary feeding interventions.Methods: In a pre-experimental study, a pretest-posttest design involving 26 wasted children aged 24-59 months was employed. The study procedures comprised product preparation, anthropometric assessments that were conducted before and after the interventions, a 10-day supplementary feeding program, and a 24-hour dietary intake recall.Results: Palata noodles could provide approximately 13% of daily caloric requirements and 30-40% of daily protein needs. Among the evaluated foods, spaghetti exhibited the highest level of food waste, while the omelet had the lowest. Statistical analysis demonstrated the significant effect of supplementary feeding on average caloric intake before and after the interventions. Additionally, dietary recall data indicated an increase in the average intake of all nutrients. Observational data showed an average weight gain of 0.7 kg among participants. It was shown that supplementary feeding had a significant impact on the body weight of toddlers before and after the interventions.Conclusion: Supplementary feeding by administration of dried noodles with Patin fish and pumpkin flour substitution significantly impacted weight gain and the intake of zinc, iron (Fe), and beta-carotene in wasted toddlers. However, no significant effect was observed on the daily intake of energy, protein, and fat among the participants.